2001
DOI: 10.1046/j.1464-410x.2001.02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased patient satisfaction from transrectal ultrasonography and biopsy under sedation

Abstract: Objective To determine the acceptability and patient satisfaction of transrectal biopsy undertaken with the patient under sedation. Patients and methods A retrospective questionnaire was sent to 100 patients who had undergone transrectal biopsy between January and August 1998. Levels of patient acceptability and satisfaction were assessed using visual analogue scales (VAS, with a maximum score of 10 being the least satisfactory or acceptable) and direct questions about the side‐effects of the procedure. A sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 13 publications
(25 reference statements)
2
49
1
1
Order By: Relevance
“…There is a general consensus regarding the necessity of some form of anesthesia during TRUS-guided prostate biopsy due to preoperative pain and/or discomfort. 7,11,12 The most common methods for alleviating discomfort during TRUS-guided biopsy are intrarectal gel or periprostatic injection. 13,14 Periprostatic nerve blocks have been reported to be effective for the reduction in discomfort, but may have limited ability to reduce Prostate biopsy under monitored anesthesia SG Kang et al 725 pain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a general consensus regarding the necessity of some form of anesthesia during TRUS-guided prostate biopsy due to preoperative pain and/or discomfort. 7,11,12 The most common methods for alleviating discomfort during TRUS-guided biopsy are intrarectal gel or periprostatic injection. 13,14 Periprostatic nerve blocks have been reported to be effective for the reduction in discomfort, but may have limited ability to reduce Prostate biopsy under monitored anesthesia SG Kang et al 725 pain.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 In addition, nerve blocks do not reduce pain during the insertion of ultrasound probes, and are even associated with increases in pain during repeated needle punctures. 17 Peters et al 7 first reported the use of propofol during prostate biopsy in 2001, but subsequent reports related to this form of sedation did not appear until 2005. This is largely due to the fact that prostate biopsies are considered minor outpatient procedures, as well as the high cost of sedation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study population was referred to our department on clinical grounds, such as a high PSA detected while investigating LUTS, or with abnormal rectal examination findings. We have previously reported an increased patient satisfaction with the use of sedation during TRUS-B, 14 and therefore all men undergoing TRUS-B in our department have propofol sedation prior to their procedure. All patients referred for a TRUS-B under sedation as a day-case procedure were informed of the nature of this study and were consented to complete the questionnaire.…”
Section: Patientsmentioning
confidence: 97%